Distinct endocytosis and immune activation of poly lactic-co-glycolic acid nanoparticles prepared by single- and double-emulsion evaporation - Spiecker, Erdmann; Hackstein, Holger; Wu, Mingjian; Scheuer, Karl; Brox, Regine; Apeleo Zubiri, Benjamin; Pusch, Lennart; Jandt, Klaus D.; Yokosawa, Tadahiro; Fischer, Dagmar (2021)
Background: Poly lactic-co-glycolic acid (PLGA) nanoparticles can be prepared by emulsion-solvent-evaporation from o/w and w(1)/o/w(2) emulsions. Aims: To elaborate similarities and differences regarding mechanical, morphological and physicochemical properties, as well as endocytosis and dose-dependent immune responses by primary human leukocytes between nanoparticles prepared by these two methods. Methods: Fluorescently labeled as well as TLR-agonist (R848)-loaded PLGA nanoparticles were prepared via both single- and double-emulsion solvent evaporation. Results: Particles prepared by both methods were similar in chemical composition and surface charge but exhibited slight differences in size and morphology. Pronounced differences were found for loading, dissolution and mechanical properties. The particles were differently endocytosed by monocytes and induced qualitatively and quantitatively different immune responses. Conclusions: Variations in nanoparticle preparation can affect particle-derived immunological characteristics.
CRIS-Team WoS Importer:2021-09-24